BREASTFEEDING TEMPORAL DISTRIBUTION TRENDS AMONG NEONATES IN TERTIARY CARE HOSPITAL IN LAHORE - Hamid Mehmood; Zarmast Khan; Abdul Rauf; Ammara Waqar (Journal of University Medical & Dental College, 2021)
ABSTRACT BACKGROUND & OBJECTIVE: Breastfeeding provides immunity against bacterial, viral, and other infectious diseases. More than four million new neonates die due to vaccine-related diseases in the first 28 days of their lives. It is therefore emphasized that breastfeeding in the first hours after delivery may save the neonate. The objective of this study was to determine the factors affecting the pattern of breastfeeding among the neonates and assess the frequency of early breastfeeding among neonates at Gulab Devi Hospital, Lahore. METHODOLOGY: It was a cross-sectional descriptive study. One hundred mothers were selected through convenient purposes sampling. Chi-square test applied for an association between mode of delivery and initiation of breastfeeding. RESULTS: The result of the study showed variability in the time of breastfeeding by the mothers from one hour to 24 hours after delivery.Pre-lacteal was given to 59 mothers, while 41 were not given with any pre-lacteal. A significant association was found between mode of delivery and initiation of breastfeeding with a p<0.001. CONCLUSION: The result of the study showed that variability in the time of breastfeeding by the mothers from one hour to 24 hours after delivery provided a significant difference in the production of the neonate in the first 28 days.